2018
DOI: 10.1123/japa.2016-0358
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior, and Physical Function in Older Adults With Multiple Sclerosis

Abstract: Older adults with multiple sclerosis (MS) experience the combined effects of aging and a chronic, disabling neurological disease on physical activity, sedentary behavior, and physical function. This study examined associations among light and moderate-to-vigorous physical activity (LPA and MVPA), sedentary behavior, and physical function in older adults with MS. Forty older adults with MS (median age = 60 years) who had a median Expanded Disability Status Scale score of 4.5 wore an accelerometer for a 7-day pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…Observing the PA intensity data of the pwMS tested, when raw accelerations were processed using the cut points proposed by Sebastiao et al [16], the percentages of SB (53%) and LPA (32%) were found consistent with those reported in previous studies which indicate values from 60 to 70% for SB and 27 to 37% for LPA [16,[42][43][44]. In contrast, our group exhibited significantly higher values for MVPA (15%), the typical values for pwMS being in the range 1-7%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Observing the PA intensity data of the pwMS tested, when raw accelerations were processed using the cut points proposed by Sebastiao et al [16], the percentages of SB (53%) and LPA (32%) were found consistent with those reported in previous studies which indicate values from 60 to 70% for SB and 27 to 37% for LPA [16,[42][43][44]. In contrast, our group exhibited significantly higher values for MVPA (15%), the typical values for pwMS being in the range 1-7%.…”
Section: Discussionsupporting
confidence: 84%
“…In particular, values of rho for correlation "speed vs. MVPA" (0.48 in our group) in the range 0.33-0.40 were reported by Cederberg et al [43] and Baird et al [44]. In contrast, Shammas et al [32] found no significant correlation between PA intensity and gait speed, but it is to be recalled that they did not use a specific cut point for pwMS to classify it.…”
Section: Discussionsupporting
confidence: 37%
“…Older adults with MS are an expanding segment of the MS population, 1 and these individuals experience a fast rate of disability progression 35 that manifests as problems with walking 2,3,8 and reduced physical 3,4 and cognitive function. 2,5 There are few options available for managing the consequences of aging with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nearly 1 million adults living with multiple sclerosis in the U.S., an estimated 43 percent are 55 years of age or older. 1 This reflects a greying of the population of adults with MS that coincides with the demographic shift of adults in the general population, and portends considerable risk for negative effects of MS and aging on walking performance 2,3 and physical 3,4 and cognitive function 2,5 as well as health-related quality of life. 6 To date, there are very few options for managing the consequences of aging with MS, 7 but some data support physical activity behavior as being associated with better walking performance, 2,3,8 physical function, 2,3 and cognitive function 2 in this particular segment of the MS population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation